EFEKTIVITAS PENGELOLAAN KEARSIPAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUKABUMI - Annisa Aulia Putri; Dian Purwanti; Tuah Nur (Kebijakan : Jurnal Ilmu Administrasi, 2023)
The title of the research is "The Effectiveness of Archives Management at the Population and Civil Registration Department of Sukabumi Regency". The research was aimed at finding out archives management effectiveness at the Population and Civil Registration Department of Sukabumi Regency. The method used in the research was quantitative method with descriptive approach. The techniques of collecting data conducted in the research were observation, questionnaire, interview and documentation. The population in the research were employees of the Population and Civil Registration Department of Sukabumi Regency. The technique of sampling deployed in the research was purposive sampling using the Slovin formula with a precision of 5% obtaining samples amounted to 66 employees. The technique of processing data in the research used SPSS (Statistical Product and Service Solutions) 25 in order to determine the validity and reliability of data, as well as hypothesis testing. The results of the research show that the effectiveness of archives management at the Population and Civil Registration Department of Sukabumi Regency gains a percentage of 83.45%; thus, the hypothesis testing obtains a value of tcount 79.271 > ttable 1.66864. Therefore, H0 is rejected and Ha is accepted. The results indicate that the Effectiveness of Archives Management at the Population and Civil Registration Department of Sukabumi Regency is considered very effective.